Paleoclimatological records of the Great Ghost Lake in Taiwan - 罗建育 陈镇东 万政康 (Science China. Earth sciences, 1997)
Distinctive white laminations appear in the black sediments of the Great Ghost Lake in Taiwan.Compared with the black sediments, these white laminations have lower porosity, organic matter content and C/N ra-tio, but higher C/S and N/S ratios, and with organic matter characterized by the phytoplanktons. It suggests thatthey may be deposited in cooler and drier periods. The organic matter of the black sediments was mainiy from landplants, suggesting deposition under warmer and wetter climates. Major white laminations appear in 0 AD, 500 AD,70D AD, 900 AD, 1 350 AD, 1 500 AD, etc., and cortespond to the periods of cold/dry and frequent dust stormsfrom the historical and natural records of China or Peru. These seem to reflect large-scale climatic changes.